Offshore platform decommissioning: The need for a cost index - Ahmed, A.B. (ISEC Press, 2014)
Globally, decommissioning of offshore installations has been considered to be one of the biggest challenges facing the oil and gas industry. International conventions on ocean safety now emphasize complete removal rather than reefing. This option is complex, requiring scarce technical expertise and environmental sensitivity in challenging environments. Both governments and operators must develop accurate cost estimates for offshore platform decommissioning. The government requires them to guide its negotiations with decommissioning contractors, while operators require them to determine annual remittances to decommissioning accounts built into modern day oil and gas concession contracts. Consequently, a reliable cost estimation method could be used to define a Zone of Possible Agreement (ZOPA) for offshore platform decommissioning in Malaysian waters before engaging in negotiations with contractors. This would improve value for money and also ensure time value for money. This article looks at current challenges concerning a proposed offshore platform decommissioning price index for Malaysian waters. The conclusion is that these indices are helpful tools for comparisons between conditions across several variables, and are easy to update once developed. Â© 2014 ISEC Press.